Distraction as a simple and effective method to reduce pain during local anesthesia: A randomized controlled trial. Issue 12 (December 2019) - Molleman, Jeroen; Tielemans, Jarl F.; Braam, Marjorie J.I.; Weitenberg, Berber; Koch, Richard
Summary: Background: The administration of local anesthetics is considered the most unpleasant part of office-based surgery. Many procedural and pharmacological strategies have been developed to minimize pain. In children and adolescents, distraction has been demonstrated to be an effective way of minimizing pain during local anesthesia. We present a randomized controlled trial of the effect of distraction on pain during local anesthesia in adults. Material and Methods: We have included 115 patients undergoing small office-based surgery to either the face, wrist, or hand. We randomized these patients between two groups: a control group and an intervention group. The intervention group watched a distractive video during the administration of the local anesthetic; for the rest the surgical procedures were performed in an equal fashion in both groups. Preoperative anxiety was scored from 0 to 10 and pain experienced during the injection of local anesthetic was measured on the visual analogue scale of pain (VAS), ranging from 0 to 10. Patient satisfaction was measured on the Patient Satisfaction Questionnaire (PSQ-18), ranging from 18 to 90. Results: Patients had an equal anticipated pain score in control and intervention group. In the intervention group, a reduction of pain scores of 1 point was observed ( p  = 0.01). There was no difference in patient satisfaction scores between both groups. Discussion: In this study, we demonstrate the pain minimizing effect of distraction during the administration of local anesthesia. Less experienced pain did not result in improved patient satisfaction in our study. We encourage physicians to seek ways to actively distract patients during unpleasant procedures.